Anechoic measurements of particle-velocity probes compared to pressure gradient and pressure microphones - WOSZCZYK, Wieslaw; IWAKI, Masakazu; SUGIMOTO, Takehiro; ONO, Kazuho; de BREE, Hans-Elias (Archives of Acoustics, 2007)
The Microflown is an acoustic particle velocity sensor invented at the University of Twente in Holland in 1994 and commercialized in 1997 [1, 9]. The sensor directly measures particle velocity rather than pressure-gradient as do most unidirectional and bidirectional microphones. The sensor has several interesting operational characteristics however few measurements of the Microflown have been published until now making it difficult for a potential user to assess the merits of this transducer in comparison to high quality condenser microphones commonly used in music and speech recording. This paper offers some insight by presenting anechoic measurements of particle velocity probes compared to the measurements of pressure-gradient and pressure microphones (of condenser type) made under identical acoustical conditions at varying distances from a point source having a wide frequency range. Detailed frequency response measurements show how the characteristics of these transducer types are dependent on their distance to the source, and highlight the need of transducer calibration with respect to distance. Very few microphone manufacturers publish frequency response data for more than one reference distance to the source although distance is often used to modify the applied response of the microphone. An additional goal for making these measurements is to establish the relationship between particle velocity and pressure gradient values using the same acoustical conditions. The measurements were made in the large anechoic chamber of the NHK Science and Technical Research Laboratories (STRL) in Tokyo during the April-May of 2006.